Предмет: Алгебра,
автор: маричик
Помогите пожалуйста очень нужно!!!!! 1. Упростите выражение : (y-4)(y+2)-(y-2)²
2. Разложите на множители : 3х³у³-3х⁴у²+9х²у²
Ответы
Автор ответа:
0
1) (y - 4)(y + 2) - (y - 2)^2 = y^2 - 2y - 8 - y^2 + 4y - 4 = 2y - 12 = 2(y - 6)
2) 3х³у³-3х⁴у²+9х²у² = 3xy(xy - x^2 + 3)
2) 3х³у³-3х⁴у²+9х²у² = 3xy(xy - x^2 + 3)
Похожие вопросы
Предмет: География,
автор: gostrobl650
Предмет: Русский язык,
автор: Аноним
Предмет: Химия,
автор: azazazhahahaha
Предмет: Математика,
автор: LelikTapo4ko